2018
DOI: 10.26719/emhj.18.001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of women applying for a legal abortion in the Islamic Republic of Iran

Abstract: Based on this law, the Iranian Legal Medicine Organization has adopted procedures in recent years for authorizing legal abortion, which require at least one of a list of 51 conditions to be met for a licence to be issued; 22 relate to the health of the mother and 29 to the health of the fetus. These 51 conditions are serious and incurable diseases that will cause the mother, the fetus or the future child to suffer (6,8,9). The Supreme Leader of Iran, Ayatollah Khamenei, issued a fatwa on this matter in 2003, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 1 publication
6
7
0
Order By: Relevance
“…Also about half of the clients with maternal and four-fifths of the clients with fetal causes received permission for abortion. In some studies that have been done before the last revision of abortion law in Iran, the rate of proportion of permission were lower (24,34,35), but the results of subsequent studies were concordant with our findings (22,(27)(28)(29)36). In addition, a study that was conducted in a hospital in Turkey demonstrated that permission for abortion was issued for 63% of cases with fetal causes (37).…”
Section: Discussionsupporting
confidence: 91%
“…Also about half of the clients with maternal and four-fifths of the clients with fetal causes received permission for abortion. In some studies that have been done before the last revision of abortion law in Iran, the rate of proportion of permission were lower (24,34,35), but the results of subsequent studies were concordant with our findings (22,(27)(28)(29)36). In addition, a study that was conducted in a hospital in Turkey demonstrated that permission for abortion was issued for 63% of cases with fetal causes (37).…”
Section: Discussionsupporting
confidence: 91%
“…Two-thirds of fetal causes that led to issuing the permission were structural anomalies and one-third of them were genetic disorders. The prevalence of the anomalies in the studies that have been conducted in different provinces of Iran was also similar to the results of the present study (22,28,29,(38)(39)(40). Also, in the study of Jose et al (2015), the most common anomalies were nervous system anomalies, chromosomal disorders, cardiovascular and skeletal disorders and hydrops (37).…”
Section: Discussionsupporting
confidence: 90%
“…Also about half of the clients with maternal and four-fths of the clients with fetal causes received permission for abortion. In some studies that have been done before the last revision of abortion law in Iran, the rate of proportion of permission were lower (24,34,35), but the results of subsequent studies were concordant with our ndings (22,(27)(28)(29)36). In addition, a study that was conducted in a hospital in Turkey demonstrated that permission for abortion was issued for 63% of cases with fetal causes (37).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Abortion may be permitted based on fetal conditions leading to afflictions for the mother due to fetal abnormalities, or based upon life-threatening maternal conditions, before ensoulment (19 weeks + 2 days) with the mother's consent. Legal abortion is allowed in 51 conditions, of which 22 are related to mother's health and 29 are related to the health of the fetus (15).…”
Section: Introductionmentioning
confidence: 99%